Assessment of Potential Ecological Risks of Cr, Cd, Pb, and As in Coastal Sediments - Nezha Mejjad; Samira El Aouidi; Abdelmourhit Laissaoui (Proceedings, 2024)
Coastal sediments are a powerful tool for analyzing pollution levels and reconstructing history. The Oualidia lagoon plays an essential role as it provides several ecosystem services, including aquaculture, fisheries, and coastal tourism, among others. Therefore, the conservation and protection of this natural system requires the continuous monitoring of its environmental quality. The present study evaluates the potential ecological risks of Cr, Cd, Pb, and As in coastal sediment cores collected from the Oualidia lagoon. These sediment cores were also dated using lead-210 to study the temporal variations in the studied metals. The potential ecological risk values of the metals show a moderate ecological risk to the lagoon since the 1950s, while the toxic units indicate low toxicity. The Adverse Effect Index (AEI) values indicate a probable effect on biota due to the concentrations of Cr, As, and Cd, mainly in the surface layers. This suggests that the development of human activities in the last two decades has contributed to increased heavy metal concentrations, leading to potential ecological risks to the lagoon. Activities such as agriculture can be potential sources of Cd. Excessive use of fertilizers and pesticides may contribute to the increase in this heavy metal in the lagoon. This finding highlights the need for the careful monitoring and remediation of Cd levels in this aquatic system, as Cd presents a high ecological risk value among the selected heavy metals.